Psychosis Biopsychosocial and Relational Perspectives - Irtelli, Floriana (IntechOpen, 2018)
This book collects chapters from a number of scientists all over the world, giving their contribution to the comprehension and clinical management of psychosis. The book adopts a perspective that respects the complexity of the human person and his/her relationships. It devotes a space both to the deepening of the more strictly biological aspects, the psychological aspects and the social aspects. Each section of the book (biological, psychological, social) reveals a deep connection with the themes of the other sections, showing the strength of this biopsychosocial interweaving. The relationship and the interweaving between these different areas is certainly a foundation of our existence and constitutes a law to which we cannot escape, so it is necessary that the biopsyosocial model is always considered in the interventions for the psychotic patient. This book also focuses on some specific and very innovative topics such as the importance of psychosocial factors and family factors, complementary approaches to psychosis managment, subclinical psychosis and relational aspects of psychosis.